TINJAUAN TENTANG TATA RIAS PENGANTIN DI KECAMATAN TALAWI KOTA SAWAHLUNTO PROVINSI SUMATERA BARAT - Pratiwi, Novika; Hayatunnufus, Hayatunnufus; Yanita, Merita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research background with many changes both face makeup, hairdo,fashion and bridal equipment and the meaning contained into it. The aims of thisstudy to describes bridal makeup in Talawi Subdistrict Sawahlunto City, WestSumatra province that see the changes that occur in makeup, hairdo, fashion andequipment, and meaning itself. The method used is descriptive method withqualitative approach, where the researcher observe the object as it is in the field.The instrument used by the researcher. Data collection techniques for this studyusing observation techniques, interviews and documentation. The results obtainedthrough data reduction, then performed the presentation of data and the lastwithdrawal of conclusions, the results of this study found that Talawi weddingmakeup ancient times very simple to use many of natural materials while nowusing modern tools, materials and cosmetics from various brands. The hairstyle ofthe bride formerly used a Lipek Pandan bun, now more practical hairstyle onlytied one back. The wedding dress has changed in terms of model, color andcomplement, although it has changed but the meaning contained there ismaintained by Talawi society.Keywords: Bridal Makeup, Makeup, Hairdo, Fashion Meaning